Abnormally high expression of HOXA2 as an independent factor for poor prognosis in glioma patients. Issue 13 (2nd July 2020) - Liu, Zhendong; Shen, Fei; Wang, Hongbo; Li, Ang; Wang, Jialin; Du, Lin; Liu, Binfeng; Zhang, Bo; Lian, Xiaoyu; Pang, Bo; Liu, Liyun; Gao, Yanzheng
ABSTRACT: In recent years, studies have revealed HOXA2 as a new oncogene, but its function is unknown in gliomas. We aimed to reveal the relationship between HOXA2 and glioma based on the Chinese Glioma Genome Atlas(CGGA) and the cancer genome atlas (TCGA). HOXA2 expression data and clinically relevant information of glioma patients were obtained from the CGGA and TCGA containing 1447 glioma tissues and five non-tumor brain tissues. The Wilcox or Kruskal tests were used to detect the correlation between the HOXA2 expression level and clinical data of glioma patients. the Kaplan–Meier method were used to examine the relationship between HOXA2 and overall patient survival. Gene set enrichment analysis (GSEA) was conducted to indirectly reveal the signaling pathways involved in HOXA2, and RT-PCR was used to detect HOXA2 expression in gliomas and non-tumor brain tissues. High HOXA2 expression was found to be positively correlated with clinical grade, histological type, age, and tumor recurrence, but negatively correlated with 1p19 codeletion and isocitrate dehydrogenase mutation status.RT-PCR results showed that HOXA2 expression levels were significantly higher in tumor tissues than in non-tumor brain tissues. GSEA showed that HOXA2 promoted the activation of the activation of the JAK-STAT-signaling pathway, focal adhesion, cell-adhesion-molecules-CAMS pathway, cytosolic DNA sensing pathway, and natural killer cell-mediated cytotoxicity. This study revealed for the first time that the novel oncogene, HOXA2, leads to poor prognosis in gliomas, and can be used as a biomarker for the diagnosis and treatment of gliomas.